If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3(y + 5) + -21 = 0 Reorder the terms: 3(5 + y) + -21 = 0 (5 * 3 + y * 3) + -21 = 0 (15 + 3y) + -21 = 0 Reorder the terms: 15 + -21 + 3y = 0 Combine like terms: 15 + -21 = -6 -6 + 3y = 0 Solving -6 + 3y = 0 Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '6' to each side of the equation. -6 + 6 + 3y = 0 + 6 Combine like terms: -6 + 6 = 0 0 + 3y = 0 + 6 3y = 0 + 6 Combine like terms: 0 + 6 = 6 3y = 6 Divide each side by '3'. y = 2 Simplifying y = 2
| 16x^2-4x+1=0 | | 4x+30=2x+82 | | 7-7/7 | | (X-5)(2x-3)(x+4)=0 | | 2(4x+4)=5 | | 0.2=ln(x+2) | | 0.2=(x+2) | | 3(3x-1)=7 | | 2x^2-11.5x=-7.5 | | -2x+22=2 | | 9w-12w+2=7 | | 1.53=logx | | f(2)=3x+4 | | 3(n+6)=15 | | 2/x^2=9.8 | | 2/(x^2)=9.8 | | p^3=25p | | 10m-15=85 | | 3x+9x+12=18+6x | | t(t-8)=-15 | | 3y+100+3x+110=360 | | 5x+2=8x+3 | | 2(2y-3x)+6-7= | | (6t^2+t)(6t^2+t)-8(6t^2+t)+7=0 | | x^2+6.25x+21.5=0 | | z=1+4i | | 9x+12y=237 | | 98-6y+2y=62 | | 3AB=4AC | | 4((49-3y)/2)/2 | | 5/11×4/9 | | 2y-14=16 |